CDNA AMPLIFIED FROM DIATOM CYCLOTELLA STRIATA TBI RNA CULTIVATED UNDER VARIOUS LIGHT CONDITIONS - Ulfah, Nurfarida
Lipids play a crucial role in microalgae and their metabolism was regulated by several enzymes related to synthesis and degradation of fatty acids (FA) and triacylglycerols (TAG) such as acetyl-CoA carboxylase (CYCst;ACC;1); glycerol-3-phosphate-acyltransferase (CYCst;GPAT;1); acyl-CoA synthetase (CYCst;ACS;1); and carnitine acyltransferase (CYCst;CAT;1). Cyclotella striata TBI is one of tropical diatom that uses lipid as food storage component. Lipid accumulation increases when exposed to external stress factors such as high light intensity and temperature, and it could be identified from the expression at the level of RNA transcript, but RNA is an unstable compound, so cDNA synthesis is carried out as an alternative. Until now, synthesis of cDNA from diatom C. striata TBI RNA grown indoor and outdoor has not been carried out. The aim of this study was to identify cDNA by RT-PCR method from diatom C. striata TBI RNA cultivated under various light conditions. Methods of this study included cultivating C. striata TBI indoor and outdoor in the modified seawater medium, total lipid extraction, designing primers for genes that involved in FA and TAG metabolism (CYCst;ACC;1, CYCst;GPAT;1, CYCst;ACS; 1, CYCst;CAT;1); identification of the amplification of these genes in genomic DNA; total RNA isolation; cDNA synthesis from total RNA; and analysis of cDNA profiles. The results showed that the initial C. striata TBI cell density of 4.8×105 cells mL?1 increased to 2.25×106 and 1.05×106 cells mL?1 both indoor and outdoor cultures with cultivation for 8 ?9 days. This is equivalent to specific growth rates of 1.78 and 1.66 d?1, or cell productivity of 2.69 and 1.52×106 cells mL?1 d?1, or biomass productivity of 71.27 and 47.95 mg L ?1 d?1. The total lipid content of C. striata TBI obtained from indoor and outdoor cultures was 32 and 49% (w/w) respectively, which equates to lipid productivity of 2.2 and 2.3 mg L?1 d?1. CYCst;ACC;1, CYCst;GPAT;1 were identified in the 500 bp DNA fragment but the CYCst;ACS;1 and CYCst;CAT;1 fragments were not identified in the genome of C. striata TBI. RNA from C. striata TBI cultures both indoor and outdoor in logarithmic and stationary phases was identified by the presence of bands measuring 1400 bp, 900 bp, 250 bp which indicated 28S, 18S, and 5S RNA respectively, with concentrations ranging from 0.8 and 1.0 mg mL?1. cDNA synthesis was successfully identified from the presence of internal controls CYCst;ACTB;1 and CYCst;RbcL;1 which were 500 bp and 750 bp, respectively. However, CYCst;ACC;1 and CYCst;GPAT;1 were not identified from the cDNA from cells cultivated indoor and outdoor both in the logarithmic and stationary phases. cDNA in these conditions has a concentration range of 1.0?1.6 mg mL?1. cDNA from C. striata TBI RNA both from indoor and outdoor cultures has high purity and concentration